Pendorong Pertumbuhan Ekonomi Regional di Jawa: Kemiskinan, Pembangunan Manusia, dan Tenaga Kerja: Studi Empiris Menggunakan Data Panel Tahun 2012 hingga 2024 - Prasetyo, Muhammad Dimas; Rivai, Aswin (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Purpose: This study aims to analyze the influence of the Poverty Gap Index (PGI), Human Development Index (HDI), and Labor Force Participation Rate (LFPR) on the growth of Gross Regional Domestic Product (GRDP) in six provinces on Java Island from 2012-2024. The study also examines the simultaneous effect of these three independent variables on GRDP growth. Design/methodology/approach: A quantitative approach was employed using panel data regression analysis. The sample consists of six provinces in Java Island over the period 2012 to 2024, with data processing conducted using Stata 17. Model selection involved the Chow Test and Lagrange Multiplier Test. Classical assumption tests included normality, multicollinearity, heteroskedasticity, and autocorrelation. Findings: The results indicate that the Poverty Gap Index has a significant negative effect on GRDP growth. The Human Development Index has no significant effect on GRDP growth. While the Labor Force Participation Rate has a significant positive effect on GRDP growth. Simultaneously, the three independent variables were found to have a statistically significant joint effect on GRDP growth in Java. Research limitations/implications: This study is limited by its inclusion of only three independent variables and less detailed supporting literature for the Poverty Gap Index. This suggests that the model's explanatory power is limited, and GRDP variations are largely influenced by factors outside the model. Practical implications: These findings highlight the importance of policies that not only reduce the number of poor but also the depth of poverty through more targeted social assistance. Improving the quality of education and health is crucial for enhancing labor productivity. Furthermore, the creation of productive employment opportunities should be encouraged to optimize labor force participation. Originality/value: This research provides empirical contributions to understanding the relationship between the Poverty Gap Index, Human Development Index, and Labor Force Participation Rate on GRDP growth in Java Island from 2012-2024, addressing previous research limitations. The use of the Poverty Gap Index offers a more sensitive measure of poverty's economic burden on marginalized groups. Paper Type: This article is quantitative empirical research paper that employs secondary data and panel data regression analysis to examine the relationship between socio-economic variables and regional economic growth in Java Island. The approach emphasizes statistical hypothesis testing and the presentation of verifiable results, providing an empirical contribution to understanding the key drivers of regional economic growth. Keywords: Poverty Depth Index , Human Development Index , Labor Force Participation Rate , GRDP , Panel Data Regression , Java Island.